Preparation Optimization of Bovine Serum Albumin Nanoparticles and Its Application for siRNA Delivery - Wang Y; Chen S; Yang X; Zhang S; Cui C (Dove Medical Press, 2021)
Yifan Wang,1– 3 Si Chen,1– 3 Xin Yang,1– 3 Shuang Zhang,1– 3 Chunying Cui1– 3 1Department of Pharmaceutics, School of Pharmaceutical Sciences, Capital Medical University, Beijing, People’s Republic of China; 2Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Beijing, People’s Republic of China; 3Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Beijing, People’s Republic of ChinaCorrespondence: Chunying Cui; Shuang ZhangDepartment of Pharmaceutics, School of Pharmaceutical Science, Capital Medical University, Number 10 Youanmenwai Street, Fengtai, Beijing, 100069, People’s Republic of ChinaTel +86-10-8391-1668; +86-10-8391-1673Fax +86-10-8391-1668; +86-10-8391-1673Email ccy@ccmu.edu.cn; zshuang@ccmu.edu.cnBackground: siRNA brings hope for cancer therapy. However, there are many obstacles for application of siRNA in clinical. Because of the excellent biocompatibility, non-toxicity and non-immunogenicity of bovine serum albumin (BSA), BSA-based nanoparticles have been widely designed as a drug carrier system.Methods: The optimal formula for BSA NPs preparation was investigated by central composite design response surface methodology (CCD-RSM), BSA-based survivin-siRNA delivery system (BSA NPs/siRNA) was characterized by dynamic light scattering, atomic force microscope, transmission electron microscope and Bradford method. The in vitro anti-tumor effect and mechanism of BSA NPs were investigated by confocal microscopic imaging, MTT assay, RT-qPCR and ELISA analysis. Moreover, the anti-tumor effect, distribution and biosafety of BSA NPs were studied in vivo.Results: The optimal formula for BSA NPs was settled to be 20 mg/mL for BSA concentration, 9 for pH value, 136% for crosslinking degree and 1.6 mL/min for speed of ethanol addition. BSA NPs/siRNA could remain stable at 4°C for 4 weeks and protect siRNA from degradation by RNase A. Besides, BSA NPs/siRNA could maintain a sustained release of siRNA and promote the uptake of siRNA significantly. The survivin-mRNA level and the survivin-protein level were decreased by 55% ± 1.6% and 54% ± 1.6% separately. The in vivo tumor inhibition results suggested that the tumor inhibition rate of BSA NPs/siRNA-treated group was 54% ± 12% and was similar with that of DOX-treated group (57% ± 9.2%, P > 0.05). The biosafety results confirmed that BSA NPs/siRNA could not induce significant damages to the main organs and blood in vivo.Conclusion: These results demonstrated that CCD-RSM was an effective tool for preparation analysis, and the BSA NPs/siRNA was a promising system for siRNA-based gene therapy.Keywords: bovine serum albumin, BSA, CCD-RSM, survivin-siRNA, nanoparticles, RNAi